2019
DOI: 10.5812/jjm.94845
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Helicobacter pylori Infection and Its Related Factors in the Tianjin Binhai Area, China

Abstract: Background: Helicobacter pylori is one of the most widely distributed and most common bacteria in the world. There is a discrepancy in the H. pylori infection rate among different regions and countries that may be due to many factors. Objectives: The study aimed to determine the current status of H. pylori infection in the Tianjin Binhai area, China, and evaluate the factors related to H. pylori infection. Methods: We recruited a sample of 2235 cases and conducted the 14 C or 13 C breath tests and questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…El sexo, el hábito de fumar y el consumo de bebidas alcohólicas son factores que suelen asociarse a la infección por H. pylori y a cáncer gástrico. En cuanto al sexo, un estudio en China refiere que la infección es ligeramente más frecuente en varones 18 , pero en Brasil, otro estudio sewww.revinf.cl…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El sexo, el hábito de fumar y el consumo de bebidas alcohólicas son factores que suelen asociarse a la infección por H. pylori y a cáncer gástrico. En cuanto al sexo, un estudio en China refiere que la infección es ligeramente más frecuente en varones 18 , pero en Brasil, otro estudio sewww.revinf.cl…”
Section: Discussionunclassified
“…La edad adulta con frecuencia es reportada como un factor asociado a la infección por H. pylori, y una de las explicaciones que algunos investigadores le dan a esta asociación es que las personas adultas suelen consumir alimentos fuera de casa o participan de actividades sociales con mucha frecuencia, lo cual incrementa su exposición 18,19 . Sin embargo, de acuerdo con los resultados de este estudio (Tabla 2), es posible que conforme se incremente la edad se reduzca el riesgo de adquirir la infección (OR 0,94; IC95% 0,90 -0,97), esto también puede encontrar explicación en el hecho de que las personas de edades más avanzadas suelen disminuir sus actividades sociales, consumen con más frecuencia medicamentos y le prestan mayor atención al cuidado de su salud y su dieta 18 .…”
Section: Investigación Clínicaunclassified
“…In the current study, the occurrence of H pylori recovered from dog stool was 62.5%. In investigation carried by [31] in China, dogs are the main home-reared animals, and it was found that the positive rate of H. pylori infection was higher in populations rearing dogs. Epidemiological data revealed that rearing dogs are a risk factor for H.pylori infection and it was inferred that dogs may be the potential storage source of bacteria [32].…”
Section: Discussionmentioning
confidence: 99%
“…Warren and Marshall first cultivated it in 1981 (4). than half of the population are infected with this pathogens and It was most common infection in the world (5) . H.pylori transmitted by contaminated water and food It acquired mainly in early childhood and may remain untreated for life, but it also can be acquired in adults (6) .…”
Section: Introductionmentioning
confidence: 99%